Mycoplasma pneumoniae-induced erythema multiforme. - Russomando, M. (European Journal of Pediatric Dermatology, 2019)
Erythema multiforme can be triggered by numerous infectious factors, including Herpes simplex, Mycoplasma pneumoniae, parvovirus B19, hepatitis A, B and C, ORF, yersiniosis, tularemia, legionnaires’ disease, adenovirus, enterovirus, influenza, paravaccinia, smallpox, poliomyelitis and vaccinations (2). Erythema multiforme is rarely encountered in the pediatric age despite the high frequency of the aforementioned infections in this age, especially Herpes simplex and Mycoplasma pneumoniae. According to some Authors (1) who examined 205 cases of the literature, erythema multiforme induced by Mycoplasma pneumoniae is characterized by important mucositis, above all involving the oral cavity, and by variable but usually not severe skin lesions; for this reason the Authors (1) proposed to call this condition “Mycoplasma-induced rash and mucositis”.